2013
DOI: 10.12954/pi.13025
|View full text |Cite
|
Sign up to set email alerts
|

Ten-core versus 16-core transrectal ultrasonography guided prostate biopsy for detection of prostatic carcinoma: a prospective comparative study in Indian population

Abstract: Purpose:To compare the cancer detection rate in patients with raised serum prostate-specific antigen (PSA) or abnormal digital rectal examination (DRE) results between the 10-core and the 16-core biopsy techniques in an Indian population.Methods:Between November 2010 and November 2012, 95 men aged >50 years who presented to the Urology Department with lower urinary tract symptoms, elevated serum PSA, and/or abnormal DRE findings underwent transrectal ultrasonography (TRUS)-guided prostate biopsy. A total of 53… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
3
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 20 publications
1
3
0
Order By: Relevance
“…Cancer detection rate was higher in both groups. Prakash et al, (2013) found higher cancer detection rate up to 59.09% in patients with PSA level greater than 20.1ng/ml [18]. In this study mean S. PSA >40 ng/ml.…”
Section: Discussionsupporting
confidence: 44%
“…Cancer detection rate was higher in both groups. Prakash et al, (2013) found higher cancer detection rate up to 59.09% in patients with PSA level greater than 20.1ng/ml [18]. In this study mean S. PSA >40 ng/ml.…”
Section: Discussionsupporting
confidence: 44%
“…One of the drawbacks of 2 D TRUS evaluation is trajectories of the samples may not be visualized, therefore accurate mapping of the prostate may not be possible. Three dimensional TRUS guided biopsies provide tracking of each sample location and precise mapping, hence lessens duplicated biopsies as may be seen with two dimensional TRUS imaging [9].…”
Section: Discussionmentioning
confidence: 99%
“…Currently available clinical diagnostic methods for prostate cancer include biochemical assay, [12][13][14][15][16][17][18][19][20] biopsy, [21][22][23][24][25][26][27] digital rectal examination (DRE), [28][29][30][31][32] and transrectal ultrasonography [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] as described in Figure 2. Among these methods, the biochemical assay is used for initial screening.…”
Section: Introductionmentioning
confidence: 99%
“…It can offer a visualization of the gland for examination and can be used to guide immediate, subsequent biopsies. [33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] Upon detecting a suspicious portion of the gland, specimens are collected. Typically, 12 specimens are collected and evaluated according to the Gleason scoring system, and the most reliable, accurate diagnosis is finally made.…”
Section: Introductionmentioning
confidence: 99%